MA’HAD AL-JAMIAH DALAM MEMBENTUK KARAKTER MAHASISWA UIN AR-RANIRY - M Jakfar Puteh; Julianto Julianto; Fazriani Fazriani (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2019)
Student character can be formed better after being fostered and guided. Therefore, UIN Ar-Raniry held Ma'had Al-Jami'ah to students who were required to attend the Ma'had Al-Jami'ah program in terms of studying religious knowledge and foreign languages (Arabic and English) with the aim of character students can become better after leaving Ma'had Al-Jami'ah. But in reality some students after leaving Ma'had Al-Jami'ah have not formed the character of students through the Ma'had program so it is not in accordance with their vision and mission. Then the researcher wants to find information about students' perceptions or responses in terms of character building programs after leaving Ma'had Al-Jami’ah UIN Ar-Raniry. This study aims to find out how high the students' perceptions about the student character formation program in Ma'had Al-Jami'ah UIN Ar-Raniry, then to find out whether there are differences in perceptions between male and female students about student character formation programs in Ma'had Al-Jami'ah UIN Ar-Raniry. The samples used in this study were 94 students of the fifth batch of two years 2017/2018 with a quantitative approach and survey method. Data collection techniques used by researchers are questionnaires and interviews as the main additional data. The data analysis technique used SPSS version 20 with a descriptive analysis research design. The results of the study prove that the 5th batch of two year 2017/2018 students have positive perceptions about the student character building program in Ma'had Al-Jami'ah UIN Ar-Raniry, this is indicated by the high percentage of students choosing statements that answer Yes 16.48%, and No 8.52% of the 25 statement items. For differences in perception between students and students can be seen from the number of average values or the mean difference value. The mean difference of women is worth 18.88841, while men are worth 19.44400. Keywords: Perception, Program, Ma'had Al-Jami’ah